Pengembangan Modul Pengecoran Logam Aluminium untuk Siswa Sekolah Menengah Kejuruan - Afiata Donny Nuryanto; Tiwan Tiwan (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
The purpose of this research is to develop aluminium casting module and to know the result of its feasibility test. In the development of this module using Research and Development method and feasibility test data obtained using questionnaire and documentation. The data obtained were analyzed using quantitative descriptive analysis in the form of scores (numbers) converted into percentages and categorized according to the scoring scale used. The aluminium casting module is produced by stages: requirements analysis, product creation, validation, product revision, product test, and product trial test analysis. The results of the feasibility test of aluminium casting module according to the material expert obtained a percentage of 76% included in the category very well. According to the media expert, aluminum casting module obtained 83% percentage included in the category very well. According to the teachers, the percentage of 87% and 88% are in the very good category, and the product test result or the student's response test to the aluminium casting module ern a percentage of 78% and 75% is included in the excellent category.Tujuan penelitian ini adalah mengembangkan modul pengecoran aluminium dan mengetahui hasil uji kelayakannya. Pada Pengembangan modul ini menggunakan metode Research and Development dan data uji kelayakan yang diperoleh menggunakan angket dan dokumentasi. Data yang diperoleh dianalisis menggunakan analisis deskriptif kuantitatif dalam bentuk skor persentase dan dikategorikan sesuai dengan skala penilaian yang digunakan. Modul pengecoran logam aluminium dihasilkan dengan tahap-tahap: analisis kebutuhan, pembuatan produk, validasi, revisi produk, uji coba produk , dan analisi hasil uji coba produk. Hasil uji kelayakan modul pengecoran logam aluminium menurut ahli materi memperoleh persentase sebesar 76% termasuk dalam kategori sangat baik. Menurut ahli media modul pengecoran aluminium memperoleh persentase 83% termasuk dalam kategori sangat baik. Menurut guru pengampu memperoleh persentase sebesar 87% dan 88 % termasuk dalam kategori sangat baik, dan hasil uji coba produk atau uji respon siswa terhadap modul pengecoran aluminium memperoleh persentase sebesar 78%  dan 75 % termasuk dalam kategori sangat baik